Penegakan Hukum Terhadap Pencemaran Sungai Akibat Limbah Industri Batik di Kelurahan Simbang Kulon Kecamatan Buaran kabupaten Pekalongan - Pramesti, Titis; Soediro, Soediro; Hidayah, Astika Nurul Hidayah Nurul (UMPurwokerto Law Review, 2024)
Abstract Batik has a high artistic value because batik as a traditional artwork and already has its identity, for areas that have traditional batik can not be separated from the development of cultural life. The main raw material for making batik is wax or commonly referred to as malam. In addition, batik is also colored using chemicals. The volume of waste from the former batik industry in the form of liquid, is increasingly unstoppable in the WWTP. In the end, the industrial waste is disposed of into rivers which causes the river to be polluted to a dark brown-black color due to the batik production process. One area with a high level of pollution is Simbang Kulon Village, Buaran District, Pekalongan Regency which is the center of the batik industry. Therefore, law enforcement efforts are needed for those who still throw batik waste into the river and make the river polluted. The purpose of this study is to find out and analyze how law enforcement efforts against river pollution due to batik industrial waste in Simbang Kulon Village, Buaran District, Pekalongan Regency are based on Pekalongan Regency Regulation Number 5 of 2014 concerning Wastewater Management and to know and analyze the inhibiting factors for law enforcement efforts. on river pollution due to batik industrial waste in Simbang Kulon Village, Buaran District, Pekalongan Regency. The method used in this research is the normative juridical method or known as the doctrinal method. This research is based on secondary data and identification and clarification of legal facts, where secondary data is obtained indirectly from the source (object of research), but through literature related to the object of research. To support research activities, data was collected through Identification and Clarification of Legal Facts with resource persons. The results of this study have carried out several law enforcement efforts against river pollution due to batik industrial waste in Simbang Kulon Village, Buaran District, Pekalongan Regency by the Pekalongan Regency Government. In an effort to enforce the law on river pollution due to batik industrial waste in Simbang Kulon Village, Buaran District, Pekalongan Regency, there are inhibiting factors both internal and external inhibiting factors. Therefore, it is necessary to make further efforts from the Pekalongan Regency Government in enforcing legal protection and taking firm action against the perpetrators who dispose of batik industry waste in the river, Simbang Kulon Village. Keywords: Law enforcement, river pollution, and waste from the batik industry. Â  Abstrak Batik dikatakan memiliki nilai seni tinggi karena batik sebagai karya seni tradisional dan telah mempunyai identitasnya. Bahan baku utama pembuatan batik ialah lilin atau biasa disebut sebagai malam.Selain itu, batik juga diberi warna menggunakan zat kimia. Volume limbah bekas industri batik yang berwujud cair, semakin tak terbendung lagi dalam IPAL. Pada akhirnya limbah industri tersebut dibuang ke sungai-sungai yang mengakibatkan sungai tersebut tercemar hingga berwarna coklat pekat kehitam-hitaman akibat proses produksi batik. Salah satu daerah yang tingkat pencemarannya tinggi adalah Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan yang menjadi sentra industri batik. Oleh karenanya, dibutuhkan upaya-upaya penegakan hukum bagi pihak-pihak yang masih membuang limbah batik ke sungai dan menjadikan sungai tersebut tercemar.Tujuan dari penelitian ini untuk mengetahui dan menganalisis bagaimana upaya penegakan hukum terhadap pencemaran sungai akibat limbah industri batik di Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan berdasarkan Perda Kabupaten Pekalongan Nomor 5 Tahun 2014 tentang Pengelolaan Air Limbah serta mengetahui dan menganalisa faktor penghambat upaya penegakan hukum terhadap pencemaran sungai akibat limbah industri batikdi Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan. Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif atau dikenal dengan metode doktrinal. Penelitian ini berdasarkan pada data Sekunder dan Identifikasi dan Klarifikasi Fakta Hukum, dimana data sekunder diperoleh secara tidak langsung dari sumbernya (objek penelitian), akan tetapi melalui pustaka yang berkaitan dengan objek penelitian. Untuk mendukung kegiatan penelitian, maka dilakukan pengumpulan data melalui Identifikasi dan Klarifikasi Fakta Hukum dengan narasumber. Hasil dari penelitian ini telah dilakukannya beberapa upaya penegakan hukum terhadap pencemaran sungai akibat limbah industri batik di Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan oleh Pemerintah Kabupaten Pekalongan. Dalam upaya penegakan hukum pencemaran sungai akibat limbah industri batik di Kelurahan Simbang Kulon, Kecamatan Buaran, Kabupaten Pekalongan terdapat faktor penghambatbaik dari internal maupun faktor penghambat eksternal.Oleh karenanya, perlu dilakukan upaya lebih lanjut dari Pemerintah Kabupaten Pekalongan dalam menegakkan perlindungan hukum dan menindak dengan tegas pelaku yang membuang limbah industri batik di sungai Kelurahan Simbang Kulon. Kata kunci: Penegakan Hukum, Pencemaran Sungai, Limbah Industri Batik.